Effects of Focus Strategies on Financial Performance of Telecommunication Companies in Kenya During the COVID-19 Pandemic: A Case of Safaricom PLC - Chege, Grace Wangui (European Scientific Journal, ESJ, 2026)
The challenges of the global business environment during the COVID-19 pandemic forced many businesses to scrutinize their competitive strategies more closely. The objective of this study was to establish the influence of focus strategies on the financial performance of telecommunication companies in Kenya using Safaricom PLC as a case study. The specific objectives of the study were to determine the influence of the focus strategy. The study used a cross-sectional design involving the management staff of Safaricom PLC. The target population was 650 employees of the Safaricom head office. The sample size was 248 employees of Safaricom PLC. Porter’s 5-force theory guided the study. The research collected primary data through a questionnaire administered to each member of the sample. A pilot study was conducted to pretest and validate the questionnaire before its administration. Both descriptive and inferential statistics were used to analyze the data collected. The data collected was then analyzed using the Statistical Package for the Social Sciences (SPSS) version 24, with descriptive statistics such as means, standard deviations, frequencies, and percentages. Regression analysis was conducted, and an ANOVA test was performed to test hypotheses and establish the best model for the study. The study found that the coefficients of the independent variables were positive and statistically significant. The study found that the focus strategy was a significant predictor of customer satisfaction (β = 0.408, p = 0.000). The ANOVA F-test p-value was less than 0.05, indicating that the overall model was significant. The analysis also indicated that the study variable was a predictor of financial performance. The study concluded that the study’s variables should be considered in the company’s decision-making. The study established that Safaricom PLC required careful market segmentation, thorough competitor analysis, and continuous monitoring of customer preferences and market dynamics to remain agile and adapt its focus strategy to evolving market trends and competitive forces, thereby sustaining long-term financial success. Focus strategy, which involved concentrating efforts and resources on a specific market segment or niche, demonstrated a positive impact on financial performance. By adopting a focus strategy, Safaricom PLC would experience improved revenue generation, higher profit margins, and an enhanced return on investment compared to those pursuing a broad-based strategy. Recent sector evidence shows that Kenya’s post-pandemic telecommunications market remains strongly shaped by broadband growth, mobile money adoption, and customer-centered digital services, with mobile data subscriptions reaching 58.5 million by June 2025 and mobile service revenue rising to KSh 425.5 billion in 2024 (Communications Authority of Kenya, 2025).